P256 A novel patient led follow up pathway following indwelling pleural catheter (IPC) insertion. (December 2018) - Rodgers, H; Walters, J; Masani, V
Abstract : Introduction and objectives: Indwelling pleural catheter (IPC) insertion is established as common clinical practice in the management of malignant pleural effusion. The Royal United Hospital (RUH) serves a population of 5 00 000 covering a large geographical area. We established an IPC service in 2010, and to date have inserted over 250 IPCs. As many patients are required to travel long distances to visit our hospital, we instigated a novel follow up policy for patients treated with malignant pleural effusions manged via IPC insertion. We offered patient choice between; a) face to face, or b) telephone consultation follow up Methods: Patients were offered a clinically based review at 4 weeks after IPC insertion, via a) pleural clinic appointment, or b) telephone consultation with a clinical nurse specialist (CNS). The CNS telephone consultation followed a clinically focused set of questions, with the outcomes for the consultation relayed to the patient's GP and recorded in the Patient Record. Patients were informed that they could contact the pleural clinic at any time prior to the 4 week review if they developed symptoms or complications related to their IPC. The system was introduced in 2015 and we reviewed outcomes for 137 patients offered these 2 follow up options. Results: Of the 137 patients, 63 opted for a telephone consultation at 4 weeks, with 74 patients opting for a pleural clinic appointment at 4 weeks. None of the 63 patients who received a telephone consultation at 4 weeks contacted our pleural clinic before their telephone consultation or developed significant post procedure difficulties which required a review in the pleural clinic. There were no clear differences between the 2 groups when observing; cancer type, distance travelled, gender and age. Conclusions: Our novel pathway illustrates that telephone consultation can enhance the ideal behind IPC placement, namely a reduction in hospital visits, without comprising care. This works particularly well for patients under active review with other specialties e.g. oncology, or who struggle to get to hospital. Our pathway also allows patients who prefer the security of face to face consultation to receive this care.